THE INFLUENCE OF DIGITAL ISLAMIC FINANCIAL LITERACY, RISK PERCEPTION, AND RELIGIOSITY ON INVESTMENT INTEREST IN ISLAMIC MUTUAL FUNDS : (A CASE STUDY ON FEBI STUDENTS OF UIN NORTH SUMATERA) - Arafah, Adinda; Nasution, Muhammad Lathief Ilhammy; Yanti, Nursantri (LPPM Universitas Trunojoyo Madura, 2025)
This study aims to analyze the influence of digital Islamic financial literacy, risk perception, and religiosity on investment interest in Islamic mutual funds among FEBI UIN Sumatera Utara students. The digital era has transformed the landscape of the Islamic financial industry, but the low level of Islamic financial literacy (9.1%) poses a challenge in the development of Islamic investment. This study uses a quantitative explanatory approach with the Structural Equation Modeling (SEM) technique based on Partial Least Square (PLS) through the SmartPLS 4 application. The research sample consisted of 98 FEBI UIN Sumatera Utara students selected using a purposive sampling technique. Data were collected through an online questionnaire with a Likert scale of 1-5. The results showed that digital Islamic financial literacy had a positive and significant effect on investment interest in Islamic mutual funds with a parameter coefficient of 0.552 and an effect size (f²) of 0.483 (a large effect). Religiosity also had a positive and significant effect, with a parameter coefficient of 0.280 and an effect size (f²) of 0.128 (moderate effect). Conversely, risk perception did not significantly influence investment interest in Islamic mutual funds, with a P-value of 0.267 and an effect size (f²) of 0.006 (very small effect). The research model was able to explain 59.8% of the variation in investment interest in Islamic mutual funds (R² = 0.598). These findings indicate that increasing digital Islamic financial literacy and strengthening religious values are more effective in encouraging investment interest in Islamic mutual funds than focusing on investment risk aspects.Keywords: Digital Islamic Financial Literacy, Risk Perception, Religiosity, Investment Interest, Islamic Mutual Funds